DEKONSTRUKSI SISTEM PATRIARKI DAN PENCARIAN IDENTITAS NOVELIS PEREMPUAN INDONESIA TAHUN 2000-AN - Wiyatmi Wiyatmi (Fakultas Sastra Universitas Negeri Malang, 2012)
This article is intended to understand the phenomena of women writers in Indonesian literature within the period of year 2000. Their works of literature emerge among the works of art dominated by male writers. Seeing through thefeminism point of view, those women writers strive their position by attempting to deconstruct the patriarch system. By producing their works, they seek their identity through the literary writing and literary critics. Their existence in Indonesian literaryworks in 2000s becomes the pioneer of women’s rebelious action against the patriarch system in Indonesian literary history. Through their works which have got some awards from Dewan Kesenian Jakarta or Khatulistiwa Awards, theircapability in writing is recognized. However, their skill in producing works of art does not necessarily get positive respond from both the society and the literary critics. There are many prickly critics which try to marginalize their works.